Near-infrared Accretion Signatures from the Circumbinary Planetary-mass Companion Delorme 1 (AB)b - S. K. Betti; K. B. Follette; K. Ward-Duong; Y. Aoyama; G.-D. Marleau; J. Bary; C. Robinson; M. Janson; W. Balmer; G. Chauvin; P. Palma-Bifani (The Astrophysical Journal Letters)
Accretion signatures from bound brown dwarf and protoplanetary companions provide evidence for ongoing planet formation, and accreting substellar objects have enabled new avenues to study the astrophysical mechanisms controlling the formation and accretion processes. Delorme 1 (AB)b, a ∼30–45 Myr circumbinary planetary-mass companion, was recently discovered to exhibit strong H α emission. This suggests ongoing accretion from a circumplanetary disk, somewhat surprising given canonical gas disk dispersal timescales of 5–10 Myr. Here, we present the first NIR detection of accretion from the companion in Pa β , Pa γ , and Br γ emission lines from SOAR/TripleSpec 4.1, confirming and further informing its accreting nature. The companion shows strong line emission, with L _line ≈ 1–6 × 10 ^−8 L _⊙ across lines and epochs, while the binary host system shows no NIR hydrogen line emission ( L _line < 0.32–11 × 10 ^−7 L _⊙ ). Observed NIR hydrogen line ratios are more consistent with a planetary accretion shock than with local line excitation models commonly used to interpret stellar magnetospheric accretion. Using planetary accretion shock models, we derive mass accretion rate estimates of ${\dot{M}}_{pla}\sim 3$ –4 × 10 ^−8 M _J yr ^−1 , somewhat higher than expected under the standard star formation paradigm. Delorme 1 (AB)b’s high accretion rate is perhaps more consistent with formation via disk fragmentation. Delorme 1 (AB)b is the first protoplanet candidate with clear (signal-to-noise ratio ∼5) NIR hydrogen line emission.